Modern Germany in transatlantic perspective - Meng, Michael; Seipp, Adam R.; Jarausch, Konrad Hugo (Berghahn Books, 2017)
"Bringing together incisive contributions from an international group of colleagues and former students, Modern Germany in Transatlantic Perspective takes stock of the field of German history as exemplified by the extraordinary scholarly career of Konrad H. Jarausch. Through fascinating reflections on the discipline's theoretical, professional, and methodological dimensions, it explores Jarausch's monumental work as a teacher and a builder of scholarly institutions. In this way, it provides not merely a look back at the last fifty years of German history, but a path forward as new ideas and methods infuse the study of Germany's past."--Provided by publisher